2020
DOI: 10.3390/ijms21020648
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Linear B-Cell Epitope on the Nucleocapsid Protein of Porcine Deltacoronavirus

Abstract: Porcine deltacoronavirus (PDCoV), first identified in 2012, is a swine enteropathogen now found in many countries. The nucleocapsid (N) protein, a core component of PDCoV, is essential for virus replication and is a significant candidate in the development of diagnostics for PDCoV. In this study, monoclonal antibodies (mAbs) were generated and tested for reactivity with three truncations of the full protein (N1, N2, N3) that contained partial overlaps; of the five monoclonals chosen tested, each reacted with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
1
16
1
Order By: Relevance
“…B-cell epitopes are an important factor in viral immunogenicity [ 33 ]. A previous study identified the B-cell antigenic epitope EP-4E88 (309KPKQQKKPK317) within the N protein [ 20 ], and this finding is inconsistent with the finding from our PDCoV/104-553/TW-2015 strain that highlighted a point mutation at the aa position (Pro-to-Ser [P310S]) (data not shown). As a highly conserved component of PDCoV, N protein mutations might dynamically alter the protein structure or antigenic recognition.…”
Section: Discussioncontrasting
confidence: 99%
“…B-cell epitopes are an important factor in viral immunogenicity [ 33 ]. A previous study identified the B-cell antigenic epitope EP-4E88 (309KPKQQKKPK317) within the N protein [ 20 ], and this finding is inconsistent with the finding from our PDCoV/104-553/TW-2015 strain that highlighted a point mutation at the aa position (Pro-to-Ser [P310S]) (data not shown). As a highly conserved component of PDCoV, N protein mutations might dynamically alter the protein structure or antigenic recognition.…”
Section: Discussioncontrasting
confidence: 99%
“…The results support the understanding of the prevalence and evolution characteristics of PDCoV in China (Zhang M et al 2019). Recent results revealed that the PDCoV EP-4E88 sequence shared very low similarity (\ 22.2%) with other porcine CoV (PEDV, TGEV, PRCV, SADS-CoV, PHEV), demonstrating that it is an epitope that can be used for distinguishing PDCoV and other porcine CoV (Fu et al 2020).…”
Section: Porcine Deltacoronavirussupporting
confidence: 78%
“…SARS-CoV-2 utilized a particular pattern to bind RNA with data on atomic resolution (Kang et al, 2020). Since N protein is a surface protein and has less variation than S protein, it can be suggested as a vaccine candidate for SARS-CoV-2 Fu et al, 2020). In silico analysis suggests that the effect of the two drugs, Glycyrrhizic acid and the phytochemical Theaflavi, on N proteins can be examined as one of the treatment options (Ray et al, 2020).…”
Section: N Proteinmentioning
confidence: 99%